Analisis Faktor Beban Tenaga Listrik di Wilayah PLN APJ Surakarta Dengan Objek Pelanggan Rumah Tangga - Adijwi, Muhammad, Umar,ST.MT (2016)
Load factor is the ratio between load average - average of the peak measured in a given period Customers distribution of electricity in the household sector are using electrical appliances at night resulting in increased consumption of electrical energy large enough or often called peak load ( WBP) so that the household sector experienced fluctuating electricity consumption than in other sectors. In the household sector customers there are several groups R1 (450 VA), R1 (900VA), R1 (1300VA), R1 (2200 VA), R2 (3500-5500 VA) and R3 (> 6600 VA). Shape patterns of electrical load in the household sector in the region Kartasura undergo considerable fluctuations, which increased during the night. This is due to electrical energy consumption dikartasura dominated by the household sector customers .. The need for electricity during peak hours had an adverse impact for all parties that need their efforts to suppress the power demand from the customer to the electrical energy consumption is really effective. This study aims to determine how much the value of the load factor that occurs in the household sector in each class residential area Kartasura. The method used to determine the value of the load factor is large comparative analysis of average power to the peak load. The results of the analysis of the data obtained that the load factor of the household sector customers R1 residential class (450 VA) 35%, R1 (900 VA) 25%, R1 (1300 VA) 20%, R1 (2200 VA) 19%, R2 (3500-5500 VA) 18%, and R3 (> 6600 VA) 14%. From these results it can be concluded that the value of the load factor on domestic customers are still fairly small enough so that the electrical energy consumption in the household sector have not maximized. The greater the load factor gained from the comparison of average power at peak load, the better because the energy provided by the system can be used to maximum. Keywords: load factor, the averge load, peak load, class residential.